New directions in copyright law - Macmillan, Fiona, LLB.; Bowrey, Kathy (Cheltenham, UK ; Northampton, MA : Edward Elgar, 2006)
This book, the third in the series, follows the themes considered in the first two volumes and brings together perspectives on copyright from law, politics, economics, cultural studies and social theory in an efforts to forge a truly coherent and meaningful agenda for the future of copyright.
Vol. 3: edited by Fiona Macmillan, Kathy Bowrey.
Description based on: t.p., v. 3, c2006.
Includes bibliographical references and index.
aug 22/05/13, ijb 28/03/2019
Loans
Keywords: Copyright